Pore structure in food : simulation, measurement and applications - Gueven, Alper (SpringerBriefs in Food, Health, and Nutrition, 2013)
The pore structure of foods directly affects the success of such food processes as drying, puffing, freeze-drying, and rehydration. Consequently, the pore structure of foods determines what types of food processes will work best with a particular food. This Brief will first discuss in depth the need to correctly measure the pore structure of foods and then will identify and describe in detail the current methods available to measure food porosity. Finally, it will review the applications of these various methods.